Family effects on the rurality of GP's work location: a longitudinal panel study - Matthew R. McGrail; Deborah J. Russell; Belinda G. O'Sullivan (BMC, 2017)
Abstract Background Reduced opportunities for children's schooling and spouse's/partner's employment are identified internationally as key barriers to general practitioners (GPs) working rurally. This paper aims to measure longitudinal associations between the rurality of GP work location and having (i) school-aged children and (ii) a spouse/partner in the workforce. Methods Participants included 4377 GPs responding to at least two consecutive annual surveys of the Medicine in Australia: Balancing Employment and Life (MABEL) national longitudinal study between 2008 and 2014. The main outcome, GP work location, was categorised by remoteness and population size. Five sequential binary school-age groupings were defined according to whether a GP had no children, only preschool children (aged 0-4 years), at least one primary-school child (aged 5-11 years), at least one child in secondary school (aged 12-18 years), and all children older than secondary school (aged ≥ 19). Partner in the workforce was defined by whether a GP had a partner who was either currently working or looking for work, or not. Separate generalised estimating equation models, which aggregated consecutive annual observations per GP, tested associations between work location and (i) educational stages and (ii) partner employment, after adjusting for key covariates. Results Male GPs with children in secondary school were significantly less likely to work rurally (inclusive of > 50 000 regional centres through to the smallest rural towns of < 5000) compared to male GPs with children in primary school. In contrast, female GPs' locations were not significantly associated with the educational stage of their children. Having a partner in the workforce was not associated with work location for male GPs, whereas female GPs with a partner in the workforce were significantly less likely to work in smaller rural/remote communities (< 15 000 population). Conclusions This is the first systematic, national-level longitudinal study showing that GP work location is related to key family needs which differ according to GP gender and educational stages of children. Such non-professional factors are likely to be dynamic across the GP's lifespan and should be regularly reviewed as part of GP retention planning. This research supports investment in regional development for strong local secondary school and partner employment opportunities.